The use of levosimendan in children with cancer with severe acute cardiac dysfunction: case series and a review of the literature. (10th May 2013) - Tosoni, Alvise; Dipchand, Anne I.; Mohseni-Bod, Hadi
Abstract We report the use of levosimendan in two febrile, neutropenic children with cancer – one post bone marrow transplant – with acute heart failure following chemotherapy. Initial management with epinephrine, milrinone, and diuresis was unsuccessful. Infusion of levosimendan without a loading dose was added to the ongoing heart failure therapy, which resulted in persistent symptomatic and echocardiographic improvement without major side effects.